Fiscal policy, income redistribution, and poverty reduction in Latin America - Nora Lustig; Valentina Martinez Pabon; Carola Pessino (Inter-American Development Bank (IDB), 2023)
This paper uses standard fiscal incidence analysis to study how much income redistribution and poverty reduction are accomplished through the fiscal system in eighteen Latin American and Caribbean (LAC) countries. We show there is considerable heterogeneity in the income inequality and poverty-reducing power of LAC fiscal systems. While all LAC fiscal systems reduce income inequality, fiscal systems in nine LAC countries are poverty-increasing, and this startling characteristic has not improved over time. When analyzing specific fiscal elements, we find that direct taxes, direct transfers, and in-kind transfers are all equalizing, and spending on education and health is often pro-poor. Moreover, contrary to expectations, indirect taxes and subsidies are more frequently equalizing than unequalizing.
Keywords: D31; D6; E62; H22; I32; 330; Fiscal policy; inequality; poverty; Latin America